77.2k views
0 votes
(3k/k-2)+(6/2-k)
3
-3
3k+6/k-2
3k+6/k+2

User Etayluz
by
5.2k points

2 Answers

5 votes

Answer: 2k

Explanation:

-k + 3k = (-1 + 3)k = 2k

User DivyaMaheswaran
by
6.0k points
5 votes

Answer:

Therefore, the answer is 3

Explanation:

The given expression is:


(3k)/(k-2) + (6)/(2-k) \\\\Taking\ LCM\\= (3k(2-k)+6(k-2))/((k-2)(2-k)) \\=(6k-3k^2+6k-12)/((k-2)(2-k))\\= (-3k^2+12k-12)/((k-2)(2-k))\\\\Applying\ formula\\=(-3(k^2-4k+4))/((k-2)(2-k))\\=(-3((k)^2-2*2*k+(2)^2))/((k-2)(2-k))\\=(-3(k-2)^2)/((k-2)(2-k))\\=(-3(k-2))/((2-k))\\=(3(2-k))/(2-k)\\=3

User Charlana
by
6.1k points